Toward a more biologically accurate model of diffusion: adhesion and collisions. (December 2017) - Fouad, Ahmed M; Noel, John A
In single-file dynamics, Brownian particles (referred to as tracer or tagged particles) diffuse and collide with each other in one-dimensional domains. If the average particle density is kept fixed during the diffusion, the collisions between the tracer particles result in their famous anomalous sub-diffusion behavior with time to the one half dependence. Many systems in nature are found to obey single-file dynamics, such as ion transport processes, and inter-particle adhesion plays a crucial role, either structurally or functionally, in the diffusion of such systems; however, the exact effect of adhesion on the diffusion has not been studied so far. We have examined the effect of adhesion on the collective diffusion of single-file systems. Here, we extend previous work where we perform large-scale numerical simulations that utilize Monte Carlo techniques and high-performance computing resources to examine the effect of adhesion on the diffusion of the tracer particles in systems that obey single-file dynamics. We show that if all the tracer particles experience the same adhesion coefficient, adhesion only slows down the diffusion by reducing the magnitude of the tracer diffusion coefficient; however, both the anomalous sub-diffusion behavior and time to the one half dependence of the tracer particles remain almost intact, independent of the adhesion.